The relationship between creamatocrit and cumulative percentage of total milk volume: a cross-sectional study in mothers of very preterm infants in Bangkok, Thailand - Walaiporn Bowornkitiwong; Chulaluk Komoltri; Sopapan Ngerncham (BMC, 2023)
Abstract Background Human hindmilk contains higher concentrations of fat than foremilk and is more desirable for growth in preterm infants who can tolerate limited volumes of breastmilk. There is currently no clear demarcation between foremilk and hindmilk. This study characterized the change in breastmilk's fat content from the start to end of milk flow and defined this demarcation. Methods Mothers of infants born at ≤ 32 weeks gestational age and ≥ 14 days after childbirth in a University hospital in Bangkok, Thailand between July, 2011, and April, 2012 were included in this cross-sectional study. Breastmilk samples were sequentially collected from the start to end of milk flow in 5-mL aliquots using breast pumps. The fat content of each aliquot from each breast was determined through creamatocrit. The average creamatocrit of foremilk and hindmilk were compared in predefined foremilk to hindmilk ratios of 20:80, 25:75, 33:67, and 50:50. Creamatocrit of the first and last aliquots were compared for mothers who expressed low- (≤ 25-mL per breast) and high-volumes (> 25-mL per breast) of breastmilk. Results Of the 25 mothers enrolled, one was excluded due to unsuccessful creamatocrit measurement. The last aliquot of breastmilk had a significantly higher creamatocrit than the first from the same breast (median [interquartile range] of 12.7% [8.9%, 15.3%] vs. 5.6% [4.3%, 7.7%]; test statistic 1128, p < 0.001). Mean creamatocrit in hindmilk portions (9.23%, 9.35%, 9.81%, and 10.62%, respectively) was significantly higher than foremilk portions (6.28%, 6.33%, 6.72%, and 7.17%, respectively) at all predefined ratios. Creamatocrit increased by 1% for every 10% incremental increase in expressed breastmilk volume until the breast was emptied. Low-volume mothers had a significantly higher creamatocrit in the first aliquot compared with high-volume mothers (U = 437, p = 0.002). No significant difference in breastmilk volume was observed between mothers with and without breastfeeding experience. Conclusions Fat content in breastmilk increased on an incremental basis. More fluid definitions of foremilk and hindmilk should be adopted. Mothers should prepare their breastmilk into aliquots based on the required feeding volume of their infant. Hindmilk aliquots can be prioritized over foremilk aliquots to ensure infants obtain optimal caloric intake.